2009
DOI: 10.1021/jm801652d
|View full text |Cite
|
Sign up to set email alerts
|

Antiseizure Activity of Novel γ-Aminobutyric Acid (A) Receptor Subtype-Selective Benzodiazepine Analogues in Mice and Rat Models

Abstract: The antiseizure activity of benzodiazepines (BDZs) 1-5 in mice and rats as animal models is described. These BDZs have selective efficacy for α2β3γ2 and α3β3γ2 GABAA-receptors. Significant anticonvulsant activity with little or no motor impairment and therapeutic indexes (TI) of 2.8-44 (mice, ip) were observed for compounds 2-4 in the subcutaneous metrazole seizure (scMET) test. In rats orally (po) the TI was >5 to 105. These compounds represent novel leads in the search for anticonvulsants devoid of sedative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 23 publications
5
61
0
Order By: Relevance
“…Both questions were addressed with conditional GABA A R deficient mice (hoxb8-α2 À/À mice), which lack the GABA A R α2 subunit specifically from the spinal cord and dorsal root ganglia (DRGs) (up to about segment C4). In these experiments, a recently developed benzodiazepine site agonists (HZ166; Rivas et al, 2009) was employed which exerts antihyperalgesic actions similar to systemic diazepam but with reduced sedative and muscle relaxant properties (Di Lio et al, 2011). Antihyperalgesia was assessed as the change in heat and pin-prick induced withdrawal responses.…”
Section: Spinal Gaba a R Subtypes Mediating Antihyperalgesia: Evidencmentioning
confidence: 99%
See 1 more Smart Citation
“…Both questions were addressed with conditional GABA A R deficient mice (hoxb8-α2 À/À mice), which lack the GABA A R α2 subunit specifically from the spinal cord and dorsal root ganglia (DRGs) (up to about segment C4). In these experiments, a recently developed benzodiazepine site agonists (HZ166; Rivas et al, 2009) was employed which exerts antihyperalgesic actions similar to systemic diazepam but with reduced sedative and muscle relaxant properties (Di Lio et al, 2011). Antihyperalgesia was assessed as the change in heat and pin-prick induced withdrawal responses.…”
Section: Spinal Gaba a R Subtypes Mediating Antihyperalgesia: Evidencmentioning
confidence: 99%
“…In addition, L-838,417 was active against hyperalgesia evoked by skin incision, a model of postoperative hyperalgesia (Reichl et al, 2012), and against capsaicin-induced central pain sensitization (Hansen et al, 2012). Other benzodiazepines with low sedative propensities include HZ166 (Rivas et al, 2009) and TPA023 (Atack et al, 2006). HZ166, which exerts rather high intrinsic activity, was antihyperalgesic in inflammatory and neuropathic mouse models (Di Lio et al, 2011), while TPA023, which is a low intrinsic activity partial agonist, showed comparatively weak anti-allodynic or antihyperalgesic effects (Munro et al, 2011;Nickolls et al, 2011).…”
Section: Antihyperalgesic Action Of Benzodiazepines With Improved Submentioning
confidence: 99%
“…HZ166 is an imidazobenzodiazepine that has been shown to possess considerable antiseizure activity induced by pentyleneterazole in both mice and rats, and anticonvulsant activity in kindled rats (Rivas et al,2009). A lack of motor impairment in rotarod indicated that this compound minimally activated α1 subunitcontaining GABA A receptors.…”
Section: Ns11394mentioning
confidence: 99%
“…HZ166 is benzodiazepine-based compound that exhibits antiseizure activities in mice and rats. 26 To determine its ability to modulate the a 1 b 3 g 2 GABA A receptor, transiently transfected HEK293T cells were first exposed to 0.3 mM GABA (EC 20 ) followed by an application of HZ166 and a co-application of HZ166 and 0.3 mM GABA. At a concentration of 30 mM, HZ166 showed a current potentiation of *200%.…”
Section: 23-25mentioning
confidence: 99%